2007
DOI: 10.1074/jbc.m705143200
|View full text |Cite
|
Sign up to set email alerts
|

Activin Regulates Estrogen Receptor Gene Expression in the Mouse Ovary

Abstract: Activin, a member of the transforming growth factor-␤ superfamily, is an important modulator of follicle-stimulating hormone synthesis and secretion in the pituitary and plays autocrine/paracrine roles in the regulation of ovarian follicle development. From a microarray study on mouse ovarian granulosa cells, we discovered that the estrogen receptor ␤ (ER␤) is inducible by activin. We previously demonstrated that estrogen suppresses activin gene expression, suggesting a feedback relationship between these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 81 publications
1
49
0
Order By: Relevance
“…These genes fall into two types of regulation of E2 actions: one is direct regulation of nER activity, which includes calmodulin (5), HSP90b (29), O-GlcNAc transferase (7), ubiquitin-conjugating enzyme E2 (UCE2) variant 1 (39), activin ␤A (11), and the dynein light chain (22,48). The second type is regulation of nER mRNA levels by such factors as PACAP (9) and activin-␤A (28). While speculative, observed changes in the expression of PACAP and activin-␤A following fadrozole treatment could potentially affect ER expression further modulating E2 actions in the brain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes fall into two types of regulation of E2 actions: one is direct regulation of nER activity, which includes calmodulin (5), HSP90b (29), O-GlcNAc transferase (7), ubiquitin-conjugating enzyme E2 (UCE2) variant 1 (39), activin ␤A (11), and the dynein light chain (22,48). The second type is regulation of nER mRNA levels by such factors as PACAP (9) and activin-␤A (28). While speculative, observed changes in the expression of PACAP and activin-␤A following fadrozole treatment could potentially affect ER expression further modulating E2 actions in the brain.…”
Section: Resultsmentioning
confidence: 99%
“…Activin is a dimeric growth factor formed by two subunits and binds the membrane serine/threonine kinase receptors (33), which then induce the activation of downstream signaling pathways and affect activities of transcriptional factors such as Smad (50). Very recently, activin signaling was shown to regulate ER␣ activity in the human breast cancer cells (11) and induce expression of ER␤ in the mouse granulosa cells (28). Moreover, E2 has been shown to regulate the expression of the activin-␤ subunits in the mouse neonatal ovary (27) and type II activin receptor in rat Hyp (56).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the important interplay between SMAD-mediated TGF-β signaling and steroid hormone nuclear receptors in mammal target tissues or organs [25][26][27]. In some species, paracrine/autocrine systems appear to be important in modulating steroid hormone control of testicular function and spermatogenesis [28].…”
Section: Discussionmentioning
confidence: 99%
“…We then identified a potential cAMP responsible element (TGACATCA) in the mouse ER variant C promoter. We further proved that this Cre motif was functional and essential for Gpr48 regulation of ER expression.Previous studies have reported that ER expression could be modulated by activin in the mouse ovary (Kipp et al, 2007) and also by prolactin in the rat corpus luteum via the Jak2-Stat5 pathway (Frasor et al, 2001;Frasor et al, 2003). In human, ER expression in osteoblast cells was upregulated by PKC/c-Src (Longo et al, 2006), and in breast carcinoma cells by ERF-1 (also known as TFAP2C), a member of the AP2 transcription factor family (McPherson et al, 1997).…”
mentioning
confidence: 99%